Successful treatment of empyema thoracis with human recombinant deoxyribonuclease. Issue 4 (1st April 2003) - Simpson, G; Roomes, D; Reeves, B
Abstract : Fibrinolytic enzymes, particularly streptokinase, are now widely used to treat empyema thoracis. Recent in vitro evidence suggests that streptokinase has no effect on pus viscosity but that deoxyribonuclease (DNase) reduces the viscosity of pus. We report the first use of human recombinant DNase given intrapleurally to treat an empyema which had not resolved after standard treatment with streptokinase.